Bias Psikologi pada Perilaku Keuangan Generasi Milenial dalam Berinvestasi di Pasar Modal - Fiorentina Dewantari; Ni Kadek Sinarwati (Universitas Sultan Ageng Tirtayasa, 2022)
As the majority of investors in Indonesia, millennials’ decision making is often influenced by psychological biases that make their decisions irrational. For this reason, this study aimed to summarize various psychological biases on the financial behavior of the millennial generation in investing in the capital market. This study used a literature study method, whereas data were obtained through a search on Google Scholar and selected using a flow chart based on inclusion and exclusion criteria. There were five articles that were used as the main data in this study. The results showed that there were various types of psychological biases that can influence investment decision making, namely herding behavior, overconfidence, disposition effect, loss aversion, conservative bias, and regret aversion. All of these psychological biases can lead investors to make adverse decisions in the future, either because of the decisions of others, overconfidence in their abilities and information, reluctant to accept losses, or simply because they were worried that they would regret it later. These biases arised because investors were influenced by their psychological and emotional factors in making decisions, rather than basing their decision making on rational quantitative analysis. Since it could lead investors to make adverse decisions, psychological biases needed to be intervened by having good financial literacy.